A project and implementation of the testing system for Intrusion Detection Systems. Part 1 - Barczak, Andrzej; Orzoł, Andrzej (Studia Informatica. System and information technology, 2009)
In the first part of the article there will be described basic terms and problems concerning IDS discipline and penetration tests. The second part of the article will show the model of the testing system of the Intrusion Detection Systems.